Pengaruh Likuiditas dan Profitabilitas Terhadap Harga Saham dengan Leverage Sebagai Variabel Intervening pada Industri Dasar dan Kimia yang Terdaftar di BEI Tahun 2018-2021 - Dian Widdyastutik; Moh. Amin; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2023)
The purpose of this study is to find out how much influence liquidity and profitability have on stock prices with leverage as an intervening variable in manufacturing companies in the basic and chemical industry sectors listed on the Indonesia Stock Exchange (IDX) 2018 - 2021. The variables in this study are liquidity and profitability as the independent variable, the stock price variable as the dependent variable and finally the leverage variable as the intervening or mediating variable. The total population in this study is 90 manufacturing companies in the basic and chemical industry sectors that are listed on the Indonesia Stock Exchange in 2018 - 2021. The sampling method uses purposive sampling using certain criteria. While the data analysis method uses path analysis using the SPSS application. The research results show that liquidity has a significant effect on leverage, profitability has no significant effect on leverage, profitability has a significant effect on stock prices, while liquidity and leverage have no significant effect on stock prices. Furthermore, the results of the intervening leverage variable are unable to mediate the effect of liquidity and profitability on stock prices. Keywords : Liquidity, profitability, leverage, stock price and intervening